PENGEMBANGAN MEDIA INTERAKTIF ARTICULATE STORYLINE BERBASIS KONTEKSTUAL PADA MATERI EKOSISTEM KELAS V SEKOLAH DASAR - Anarli, Anarli; Hermita, Neni; Putra, Zetra Hainul (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2023)
The development of science and technology is developing so rapidly that teachers have to keep abreast of technological developments in learning. This study aims to develop a product in the form of interactive media articulating contextual-based storylines on ecosystem material for fifth-grade students that is valid and practice. This type of research is research and development which is carried out through the ADDIE model. The research stages of the ADDIE model include Analysis, Design, Development, Implementation and Evaluation. The main technique in this study is the validity and practicality analysis of interactive media. The data is then processed through quantitative and qualitative analysis techniques. The results of the assessment of the validity of the interactive media are obtained with an average value of 76% which is in the valid category. The results of the teacher's practicality assessment show an average score of 80% which is in the practical category. Assessment of the value of practicality by students is obtained with an average value of 89.9% in the very practical category. Based on the results of this study, the product of this research development in the form of contextual-based articulate storyline interactive media on ecosystem material for fifth-grade students was declared to have met the validity and practicality categories so that this product could be used by teachers and students in classroom learning.